REN C-5312T, but not C-5434T, correlates to increase serum angiotensin I level in angiotensin II receptor blockers-treated hypertensive patients (Bangladesh Journal of Pharmacology, 2016)
Renin distal enhancer plays a crucial role in regulating renin gene (REN) expression. REN C-5312T enhancer polymorphism increased enhancer activity. REN C-5434T was also identified which supposed to part of enhancer region. Therefore, this study aimed to investigate contribution of both C-5312T and C-5434T to serum angiotensin I in response to angiotensin II receptor blockers (ARB). C-5312T was identified in 46 hypertensive patients by using multiplex polymerase chain reaction (PCR), while C-5434T by using PCR-restiction fragment length of polymorphism (RFLP). Angiotensin I was measured using enzyme linked immunosorbent assay (ELISA). A significant difference of baseline angiotensin I was observed between -5312CC and -5312CT/TT (p=0.038) as well as the angiotensin I after 5 months of ARB treatment (p=0.008) in -5434CT/TT population, but not REN C-5434T. In conclusion, C-5312T resulted in increased mRNA renin level as consequence of higher enhancer activity not only at the baseline but also after 5 months ARB treatment.